A Comparative Study of Fluency and Accuracy in Second Language Speaking for The Tenth Grade of SMKN 1 Tapaktuan - Yulita Halim (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study explores the relationship between fluency and accuracy in second language speaking among the tenth grade students of SMKN 1 Tapaktuan enrolled in English as a Foreign Language (EFL) programmes. Adopting a descriptive comparative approach, the research examines how different instructional orientations—communicative-focused and grammar-focused teaching—shape patterns of oral performance. 26  students from two classes participated in speaking tasks consisting of monologic and dialogic activities, followed by semi-structured interviews. Speaking performances were evaluated using analytic rubrics assessing continuity of speech, hesitation patterns, grammatical control, and lexical appropriateness. The findings indicate contrasting tendencies between the two groups: learners exposed to communicative-oriented instruction demonstrated greater fluency and interactional flow, whereas those receiving grammar-focused instruction exhibited stronger linguistic accuracy. The study highlights the pedagogical tension between meaning-focused communication and attention to form, suggesting that balanced instructional design may better support holistic speaking development. By situating the analysis within the Indonesian EFL context, this research contributes to applied linguistics discussions on how classroom practices influence oral proficiency.